Exploring inequalities in HPV vaccine uptake among Cape Verdean immigrant and Portuguese native women - Alarcão, V. (2021)
Based on data from the FEMINA study, this communication aims to explore inequalities in HPV vaccine uptake. Results highlighted differences between the Portuguese and the Cape Verdean women: 97% vs. 67% had heard about the HPV vaccine; 30% vs. 9% had been vaccinated, and 71% vs. 82% had reported a lack of medical recommendation as a major reason for not having been vaccinated. Further research on the mechanisms that operate in the production of health disparities is needed to promote equity-focused interventions.